2011
DOI: 10.1111/j.1526-100x.2009.00565.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Establishment of a Native Grass Reduces the Competitive Effect of a Non‐Native Grass

Abstract: Buffelgrass (Pennisetum ciliare (L.) Link), a C 4 perennial bunchgrass native to Africa and parts of Asia, has invaded broadly across the southwestern United States and northern Mexico. Buffelgrass establishment may occur earlier than the natives it displaces which may preempt resource acquisition by native species and contribute to its invasion success. In a greenhouse, buffelgrass aboveground growth was tested against Arizona cottontop (Digitaria californica (Benth.) Henr.), a native C 4 perennial bunchgrass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 39 publications
6
33
0
Order By: Relevance
“…Differences in the arrival of a species or phenological timing can produce priority effects (Grman and Suding 2010) which have been found to influence competitive ability (Dickson et al 2012). Several studies have examined the relationship between competition and priority effects (Abraham et al 2009;Grman and Suding 2010;Stevens and Fehmi 2011;Dickson et al 2012). Seasonal priority effects may allow exotic species to fill a vacant phenological niche by growing earlier in the season than native species (Wolkovich and Cleland 2011;Wainwright et al 2012).…”
Section: Introductionmentioning
confidence: 97%
“…Differences in the arrival of a species or phenological timing can produce priority effects (Grman and Suding 2010) which have been found to influence competitive ability (Dickson et al 2012). Several studies have examined the relationship between competition and priority effects (Abraham et al 2009;Grman and Suding 2010;Stevens and Fehmi 2011;Dickson et al 2012). Seasonal priority effects may allow exotic species to fill a vacant phenological niche by growing earlier in the season than native species (Wolkovich and Cleland 2011;Wainwright et al 2012).…”
Section: Introductionmentioning
confidence: 97%
“…So far experiments manipulating plant species order of arrival have mainly used controlled experimental set-ups using pots or mesocosms (Ejrnæs et al, 2006; Chase, 2010; Moore and Franklin, 2011; Stevens and Fehmi, 2011; Dickson et al, 2012; Byun et al, 2013; Kardol et al, 2013; Mason et al, 2013; Ulrich and Perkins, 2014; Burkle and Belote, 2015; Wilsey et al, 2015; Sikes et al, 2016). Focusing on order of arrival of different PFGs, Körner et al (2008) set up an experiment with nine grassland species from three different groups (non-leguminous forbs, legumes, and grasses), sowing one group before the other two.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies testing priority effects by altering order of arrival compared effects of exotic and native competition both in the field (Chadwell and Engelhardt, 2008; Goldstein and Suding, 2014; Young et al, 2014; Vaughn and Young, 2015) and in controlled experiments (Grman and Suding, 2010; Stevens and Fehmi, 2011; Mason et al, 2013). These studies generally found that small differences in emergence timing can have long-lasting effects on community structure, and that initial control of exotics can increase the establishment of native perennial seedlings.…”
Section: Introductionmentioning
confidence: 99%
“…Whether cultivars and hybrids are able to establish over the long-term and may invade into already existing native vegetation needs again further research. As plant–age-relationships are known to play an important role in the outcome of competition [36], further studies should also focus on competition between “invading” cultivars or hybrids and established wilds as well as further species from the native vegetation.…”
Section: Discussionmentioning
confidence: 99%